2004
DOI: 10.3109/10929080500163547
|View full text |Cite
|
Sign up to set email alerts
|

Safe femoral pin placement in knee navigation surgery: A cadaver study

Abstract: A number of navigation systems used for total knee replacement surgery currently require the insertion of a distal femoral reference sensor pin, which is placed anterior to posterior just superior to the level of the knee joint. There is potential for the posterior neurovascular bundle to be damaged during the insertion of this sensor device. The aim of this cadaveric study was to identify the structures at risk during insertion of the distal femoral sensor, and determine whether a safe zone for insertion coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In one anatomic study, the findings indicated the close proximity of the popliteal vessels to potential injury with bicortical placement of tracker pins in the anteroposterior direction in typical total knee approaches [13]. They reported that 100% of pins placed in the distal femur from anterolateral to posterior medial were within 5 mm of the popliteal artery and vein.…”
Section: Discussionmentioning
confidence: 99%
“…In one anatomic study, the findings indicated the close proximity of the popliteal vessels to potential injury with bicortical placement of tracker pins in the anteroposterior direction in typical total knee approaches [13]. They reported that 100% of pins placed in the distal femur from anterolateral to posterior medial were within 5 mm of the popliteal artery and vein.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to have a clear understanding of the relationship between the neurovascular structures posterior to the knee joint when considering surgery in this area. Marchant et al [15] observed the existence of a definite, reproducible risk to the popliteal neurovascular structures when placing a bicortical reference pin. The popliteal artery and vein were observed to be most at risk due to their apparent intimate relationship to the posterior femoral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the potential for damage to neurovascular structures during knee surgery has been identified [9][10][11][12][13][14]. Marchant et al demonstrated that 100% of pins placed in the distal femur from anterolateral to posterior medial were within 5 mm of the popliteal artery and vein [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there may be a risk of injuring the patellofemoral joint and neurovascular bundle while placing the blocking screws in an anteroposterior direction. 2,3 Does the screw location differ depending on the pattern of the fracture? What was the authors' view regarding this issue?…”
Section: To the Editormentioning
confidence: 99%